Bombyx mori silk/titania/gold hybrid materials for photocatalytic water splitting: combining renewable raw materials with clean fuels - Krüger, Stefanie; Schwarze, Michael; Baumann, Otto; Günter, Christina; Bruns, Michael; Kübel, Christian; Szabó, Dorothée Vinga; Meinusch, Rafael; Bermudez, Verónica de Zea; Taubert, Andreas (Beilstein Journal of Nanotechnology, 2018)
The synthesis, structure, and photocatalytic water splitting performance of two new titania (TiO2)/gold(Au)/Bombyx mori silk hybrid materials are reported. All materials are monoliths with diameters of up to ca. 4.5 cm. The materials are macroscopically homogeneous and porous with surface areas between 170 and 210 m2/g. The diameter of the TiO2 nanoparticles (NPs) – mainly anatase with a minor fraction of brookite – and the Au NPs are on the order of 5 and 7–18 nm, respectively. Addition of poly(ethylene oxide) to the reaction mixture enables pore size tuning, thus providing access to different materials with different photocatalytic activities. Water splitting experiments using a sunlight simulator and a Xe lamp show that the new hybrid materials are effective water splitting catalysts and produce up to 30 mmol of hydrogen per 24 h. Overall the article demonstrates that the combination of a renewable and robust scaffold such as B. mori silk with a photoactive material provides a promising approach to new monolithic photocatalysts that can easily be recycled and show great potential for application in lightweight devices for green fuel production.
Keywords: Bombyx mori silk; gold; photocatalytic water splitting; titania